Carbon Capture from Natural Gas Flue Emissions and Air via (Bi)Carbonate Formation in a Cyclodextrin-Based Metal-Organic Framework - Lim, S. Alexandra; Zick, Mary E.; Kim, Jaehwan; Rhodes, Benjamin J.; Randrianandraina, Joharimanitra; Pitt, Tristan A.; Jerozal, Ronald T.; Lee, Jung-Hoon; Forse, Alexander C.; Milner, Phillip J. (American Chemical Society, 2025)
Carbon capture and utilization or sequestration (CCUS) from industrial point sources and direct air capture (DAC) are both necessary to curb the rising atmospheric levels of CO2. Amine scrubbers, the current leading carbon capture technology, suffer from poor oxidative and thermal stability, limiting their long-term cycling stability under oxygen-rich streams such as air and the emissions from natural gas combined cycle (NGCC) power plants. Herein, we demonstrate that the hydroxide-based cyclodextrin metal-organic framework (CD-MOF) Rb2CO3 CD-MOF ST possesses high CO2 capacities from dry dilute streams at low temperatures and humid streams at elevated temperatures. Additionally, it displays good thermal, oxidative, and cycling stabilities and selective CO2 capture under mixed gas conditions in dynamic breakthrough experiments. Unexpectedly, under dry, hot conditions, a shift in the CO2 adsorption mechanism-from reversibly formed bicarbonate to irreversibly formed carbonate-is observed, as supported by gas sorption and spectroscopic studies coupled with density functional theory (DFT) calculations. This mechanistic switch, akin to urea formation in amine-functionalized sorbents, has not been previously reported in a hydroxide-based material and sheds new light on the interplay between bicarbonate and carbonate species during CO2 capture. Our findings provide valuable insight for the design of next-generation materials containing oxygen-based nucleophiles for carbon capture applications.